Analisis SWOT Strategi Pengembangan Usahatani Padi di Kecamatan Ranteangin, Kabupaten Kolaka Utara - Kajedo, Akbar; Dewi Marwati Nuryanti; Irwan Halid (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
This study aims to develop a rice development strategy in Ranteangin District, North Kolaka Regency, by utilizing local potential while addressing various challenges faced by farmers. The analysis was conducted using the IFAS, EFAS, and SWOT matrices to identify strengths, weaknesses, opportunities, and threats. The analysis results indicate that the position of rice development is in quadrant V of the IE Matrix, which indicates the need for a hold and hold strategy through increasing internal efficiency, optimizing resources, and utilizing external opportunities. The formulated strategic priorities include maximizing land and irrigation utilization with the support of subsidies and agricultural programs, increasing farmer capacity through training and extension on agricultural modernization, strengthening sustainable market partnerships, and diversifying farmer income sources. The implementation of this strategy is expected to increase productivity, competitiveness, and economic resilience of farmers, while encouraging the failure of rice farming businesses in Ranteangin District. This study also recommends a synergistic role between local governments, agricultural extension workers, farmer groups, farmers, as well as researchers and academics in supporting the success of rice development based on local potential.